Determinants of Technical Efficiency in Indonesian Manufacturing: The Case of Motor-Vehicle Firms - Prasethea, Kevin Fernanda; Suyanto, Suyanto; Sundari, Made Siti (Muhammadiyah University Press, 2020)
This current study analyses the technical efficiency of Indonesian motor vehicle manufacturing firms (ISIC 34100) and its selected important determinants. The technical efficiency scores are calculated using Data Envelopment Analysis (DEA) and the estimation on the determinants employs the panel data method. The output variable is the total value of output for each firm, whereas the input variables are material, workers, capital, and energy. The selected determinants affecting technical efficiency are export, import, capital-labour ratio, and foreign ownership. It is found that the average technical efficiency score under VRS is 0.81 during the period 2007-2013, with the lowest score is 0.53 in 2010 and the highest score is 0.89 in 2012. The findings from the estimation of important determinants show that export, capital-labour ratio, and foreign ownership provide a positive significant effect on the technical efficiency respectively. In contrast, import has a positive insignificant effect on the technical efficiency.